Inosiplex for Localized Herpes Zoster in Childhood Cancer Patients: Preliminary Controlled Study - Feldman, S. (1978)
By multiple criteria, inosiplex—a reputed stimulator of virus-sensitized lymphocytes—had no demonstrable therapeutic effects in a preliminary controlled study of patients with localized herpes zoster and cancer. Lymphocytes from the six drug-treated patients were no more responsive to varicella-zoster antigen and phytohemagglutinin than were lymphocytes from seven patients who received a placebo.